2010
DOI: 10.1093/neuonc/nop061
|View full text |Cite
|
Sign up to set email alerts
|

Gliomas display a microRNA expression profile reminiscent of neural precursor cells

Abstract: Gliomas express many genes that play a role in neural precursor cells (NPCs), but no direct comparison between glioma and stem cell (SC) gene expression profiles has been performed. To investigate the similarities and differences between gliomas and SCs, we compared the microRNA (miRNA) expression signatures of glial tumors, embryonic SCs (ESCs), NPCs, and normal adult brains from both human and mouse tissues. We demonstrated that both human gliomas (regardless of their grade) and methylcholanthrene-induced mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 49 publications
8
110
1
2
Order By: Relevance
“…miR-146a is unique in that it is significantly enriched in the human tissues of skin (melanoma), cervical, breast, pancreas and prostate cancers compared to the same noncancerous tissues (42,51,53). Similarly, miR-146a was also upregulated in human glioblastoma tissues and in both human and mouse primary glioma cell lines (32). In this regard, increased expression of miR-146a can be viewed as a biomarker for cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-146a is unique in that it is significantly enriched in the human tissues of skin (melanoma), cervical, breast, pancreas and prostate cancers compared to the same noncancerous tissues (42,51,53). Similarly, miR-146a was also upregulated in human glioblastoma tissues and in both human and mouse primary glioma cell lines (32). In this regard, increased expression of miR-146a can be viewed as a biomarker for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Among these miRNAs, miR-146a, miR-182, miR-183, and miR199a-3p are shown to be enriched in diverse cancers, whereas miR-127 and miR-140 are downregulated in gliomas (32,46). In contrast to the unchanged expression of miR-146b, miR146a was significantly induced by EGFR vIII alone or in combination with ablation of Pten (Fig.…”
Section: Egfr Activation and Pten Inactivation Synergistically Inducementioning
confidence: 95%
“…63 demonstrated that gliomas display neural precursor cell (NPC)‐like miRNA signatures. In a human glioma panel, 71 of the 180 miRNAs investigated had a distinct expression pattern which matched that of the embryonic stem cells and neural precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…These clusters comprise the miR17 family, miR183-182, and the SC-specific clusters (miR367-302 and miR371-373), which are upregulated in gliomas. Because the massive cluster of 53 miRNAs on chromosome 14q32.31 is downregulated, it may represent the largest tumor suppressive miRNA cluster 20 . Some of these clusters, such as miR17-92, which is one of the three miRNA clusters related to the miR-17 family, reportedly have a pro-oncogenic roles in other type of cancers 21 .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that gliomas share miRNA expression profiles that are similar to neural precursor cells 20 . This result is in agreement with the finding that gliomas contain heterogeneous neoplastic cell populations that phenotypically resemble undifferentiated or immature glial cells.…”
Section: Introductionmentioning
confidence: 99%